Psychiatric disorders following hysterectomy (Bangladesh Journal of Psychiatry, 2018)
Hysterectomy is one of the most commonly performed gynecological surgical procedures on the uterus which are thought to be an insult to the women’s emotional equilibrium. It leads to the feeling of reduced femininity which may develop psychiatric disorders. The objective of the study was to evaluate the proportion and pattern of psychiatric disorders among the hysterectomized women. This was a cross sectional and comparative study, conducted in the department of Psychiatry in collaboration with the outpatient department of Gynecology and Obstetrics, Sylhet MAG Osmani Medical College Hospital, Sylhet, Bangladesh during the period from January 2012 to December 2012. For this purpose 365 married women of reproductive age group, after 3 to 6 months of planned hysterectomy fulfilling the inclusion and exclusion criteria were selected consecutively as a case group and age matched 365 healthy women were selected as control group. The result showed that, the mean age of the respondents was 41.48 (SD±3.79) years which was almost identical to control group (p=0.953). Most (49.5%) of the women were below the age of 40 years. Psychiatric disorders were most frequent in hysterectomized group (38.3%) as compared to control group (28.1%) (p